Indonesian Newcastle Disease Virus Field Isolate Reduces c-Jun Expression in Rat Mammary Cancer Models - Marson, Fransiska Gratia Sonita; Sewoyo, Palagan Senopati; Astawa, I Nyoman Mantik; Adi, Anak Agung Ayu Mirah; Suardana, Ida Bagus Kade; Winaya, Ida Bagus Oka; Berata, I Ketut (Media Kedokteran Hewan, 2025)
c-Jun is often found to be overexpressed in various cancers, so this gene might be a target for cancer therapy. Newcastle disease virus (NDV) is recognized for its oncolytic properties and potential as a cancer virotherapy agent, with various mechanisms reported to trigger cancer cell death. This study aimed to assess the c-Jun expression in rat mammary cancer models. Rat mammary cancer models were categorized into two treatment groups: the control group (C) and the virotherapy group (V). Group C was administered with 0.5 cc of sterile PBS, while group V received 7 log 2 HAU per 0.5 cc of the Indonesian NDV field isolate Tabanan-1/ARP/2017 intratumorally. The treatment was carried out for four days in a row. Two weeks after treatment, all rats were humanely euthanized, and mammary cancer tissues were excised for further examination. Mammary cancer tissues were examined histopathologically and analyzed using immunohistochemistry to determine intranuclear c-Jun expression, quantified by the H-Score. The results demonstrated that NDV significantly reduced c-Jun expression. It can be inferred that NDV Tabanan-1/ARP/2017 holds potential as a mammary cancer therapy agent by reducing c-Jun expression. This finding is considered novel, as there have been no previous reports of decreased c-Jun expression following virotherapy with NDV.